2009
DOI: 10.1002/adma.200802213
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge‐Based Approach towards Hydrolytic Degradation of Polymer‐Based Biomaterials

Abstract: The concept of hydrolytically degradable biomaterials was developed to enable the design of temporary implants that substitute or fulfill a certain function as long as required to support (wound) healing processes or to control the release of drugs. Examples are surgical implants, e.g., sutures, or implantable drug depots for treatment of cancer. In both cases degradability can help to avoid a second surgical procedure for explanation. Although degradable surgical sutures are established in the clinical practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(99 citation statements)
references
References 76 publications
2
92
0
5
Order By: Relevance
“…The study therefore comprised an overall number of 45 simulated models. While some of the results mentioned below for the homopolyesters were already discussed elsewhere [15,16,20], detailed results for the copolyesters are shown and discussed in comparison with the homopolymers for the first time in the current paper. Utilizing the structural snapshots in the recorded history files the following model properties were calculated for all models mentioned in Table 2 considering all above described water contents: water accessible fractional free volume, mean squared displacements (MSD) which are characterizing the respective diffusion for the polymer atoms and the inserted water molecules (where available), cohesive energy densities CED and related solubility parameters δ = (CED) 1/2 for all polymer models, in each case with and without inserted water molecules.…”
Section: Molecular Modeling Approachmentioning
confidence: 79%
“…The study therefore comprised an overall number of 45 simulated models. While some of the results mentioned below for the homopolyesters were already discussed elsewhere [15,16,20], detailed results for the copolyesters are shown and discussed in comparison with the homopolymers for the first time in the current paper. Utilizing the structural snapshots in the recorded history files the following model properties were calculated for all models mentioned in Table 2 considering all above described water contents: water accessible fractional free volume, mean squared displacements (MSD) which are characterizing the respective diffusion for the polymer atoms and the inserted water molecules (where available), cohesive energy densities CED and related solubility parameters δ = (CED) 1/2 for all polymer models, in each case with and without inserted water molecules.…”
Section: Molecular Modeling Approachmentioning
confidence: 79%
“…22 Generally, implants which are degradable in vivo with an appropriate degradation rate allow host tissue growth until healing is complete, while eliminating the need for a second operation to remove the implant. 11,23 In this study, the n-CDHA-MAC composites with 30 wt% and 40 wt% exhibited suitable degradation in phosphate-buffered solution over time, and the mechanical strength of the 30 wt% n-CDHA composite was higher than that of the 40 wt% specimen after soaking for 12 weeks. Therefore, it could be suggested that the composite with 30 wt% n-CDHA has the potential to provide enough mechanical strength to meet the fundamental requirements of a bone substitute.…”
Section: Mechanical Propertiesmentioning
confidence: 94%
“…All polymeric materials degrade to some extent when in contact with the human body environment. Polymer implants, under normal circumstances, always undergo abrasion and stress (Hofmann et al, 2009). Poor long-term properties such as low resistance to wear and mechanical stress result in discomfort or pain for the patient, or costly replacement operations.…”
Section: Polymeric Materials In Medical Applicationsmentioning
confidence: 99%